2022
DOI: 10.1017/s0033291722002604
|View full text |Cite
|
Sign up to set email alerts
|

Network modeling of major depressive disorder symptoms in adult women

Abstract: Background Major depressive disorder (MDD) is one of the growing human mental health challenges facing the global health care system. In this study, the structural connectivity between symptoms of MDD is explored using two different network modeling approaches. Methods Data are from ‘the Virginia Adult Twin Study of Psychiatric and Substance Use Disorders (VATSPSUD)’. A cohort of N = 2163 American Caucasian female-female twins was assessed as part of the VATSPSUD study. MDD symptoms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
(74 reference statements)
1
3
0
Order By: Relevance
“…DAG analyses also implicated the presence of insomnia as probabilistically dependent on the presence of both fatigue and poor self-esteem. These ndings are in line with existing centrality ndings of depressed mood, fatigue, and self-esteem symptoms emerging across Western [90,[97][98][99] and Eastern cultures [100][101][102]. Furthermore, other ndings implicated depressed mood directly leading to fatigue [47] or indirectly impacting insomnia through fatigue [103].…”
Section: Discussionsupporting
confidence: 85%
“…DAG analyses also implicated the presence of insomnia as probabilistically dependent on the presence of both fatigue and poor self-esteem. These ndings are in line with existing centrality ndings of depressed mood, fatigue, and self-esteem symptoms emerging across Western [90,[97][98][99] and Eastern cultures [100][101][102]. Furthermore, other ndings implicated depressed mood directly leading to fatigue [47] or indirectly impacting insomnia through fatigue [103].…”
Section: Discussionsupporting
confidence: 85%
“…In the DAG analysis (Fig. 2 , Table 3 ), the strength of the association between two items is denoted by the thickness of the edge, as stated above 91 . Table 3 lists the edge weights (from strongest to weakest).…”
Section: Resultsmentioning
confidence: 99%
“…The directions of the edge weights indicate the increase or decrease in a given score that would be expected if the arc were removed from the DAG 92 . If two items are strongly related, the edge weight will be negative and its absolute value will be large 91 .…”
Section: Resultsmentioning
confidence: 99%
“…They utilized conditional probabilistic reasoning to predict the likelihood of long hospital stays in patients under different circumstances, aiming to enhance the prognosis of trauma patients and reduce medical costs. Additionally, Moradi et al [ 25 ] explored potential directional relationships between symptoms of major depression using directed acyclic graphs and Bayesian networks. They revealed the highest centrality of depressive mood symptoms and suggested that body weight and appetite symptoms exhibited the strongest connection in the network.…”
Section: Introductionmentioning
confidence: 99%